Nanoseed-assisted rapid formation of ultrathin ZnO nanorods for efficient room temperature NO2 detection. Issue 14 (1st November 2016) - Xia, Yi; Wang, Jing; Li, Xian; Dan Xie; Zhou, Dali; Xiang, Lan; Komarneni, Sridhar
Abstract: The influence of ZnO nanoseeds on the formation of ZnO nanorods from ε-Zn(OH)2 in NaOH solution at 80 °C was investigated, using ZnO nanoparticles with a diameter of 4–10 nm as the seeds. The experimental results indicated that the presence of ZnO nanoseeds promoted the rapid heterogeneous formation of ultrathin ZnO nanorods. Compared with the ZnO submicron rods with a diameter of 0.5–1.0 µm, the ultrathin ZnO nanorods with a diameter of 10–15 nm were found to be more sensitive for detecting NO2 at room temperature owing to their higher variation of channel conduction to the diameter.